Nanocellulose reinforced zeolite based geopolymer concrete: density analysis through response surface methodology - Tay, Chai Hua; Mazlan, Norkhairunnisa; Wayayok, Aimrun; Basri, Mohd Salahuddin; Mustafa, Mohd; Abdullah, Albakri (Elsevier, 2022)
Geopolymer Foam Concrete (GFC) is an emerging concrete with environmentally friendly properties but excellent strength. Currently, research is ongoing in producing GFC with low densities for its lightweight, subsidized handling and transportation cost. However, they are often fabricated with high molarity alkaline solution. In addition to that, studies related to geopolymers are often limited to one-factor-a-time (OFAT) approach. In this study, Response Surface Methodology (RSM) is used to analyze the relationship between several factors selected and its response (density). The factors involved include Seawater/Potassium Silicate (SW/KSil), Potassium Hydroxide/Potassium Chloride (KOH/KCl), Sodium Laureth Ether Sulfate/Benzalkonium Chloride (SLES/BAC), and Hydrogen Peroxide/Nanocellulose (H2O2/Nanocellulose). The concentration of alkaline solution is maintained at low level to promote user friendly and environmentally friendly properties. It was found that all factors are significant with ρ-value < 0 except for SW/KSil with ρ < 0.474. Contour plots of KOH/KCL and H2O2/Nanocellulose produce the widest range of geopolymer density, ranging from <1.5 g/cm3 to >2.4 g/cm3 While high H2O2 amount is needed to produce GFC with low density, nanocellulose is helpful in maintaining the viscosity of slurry to allow stable formation of pores. Ultra-lightweight GFC with densities <1.5 g/cm3 has been successfully produced through this research.